Mesoclimatic analysis of non-precipitation periods in Lithuania - Ūselytė, Joana; Bukantis, Arūnas (Journal of Environmental Engineering and Landscape Management, 2023)
In this paper, climatic analysis of non-precipitation periods (NPP) in Lithuania was performed, assessing their recurrence and trends from 1991 to 2020 using two criteria – when precipitation was